Rohdea tuberculata (Asparagaceae), a new species from Central Sichuan, China - Feng, Hui Zhe; Ying, Zhao Yan; Hui, Bi Ming; Hui, Li Wen; Chen, Jing (Phytotaxa, 2023)
Rohdea tuberculata is described and illustrated as a new species from Sichuan province of China. In the new species the blade elliptical, perianth lobes reflexed, and the stamen filaments are obvious, ca. 3 mm long and strongly curved. In these features, the new species is morphologically similar to R. wattii but differs in larger blade (ca. 40×15 cm), perianth lobes densely with tuberculate protrusions, longer tube (ca. 10 mm long) and the stigma below the base of the free part of the filaments.